Impact of Diabetes on Platelet Function in Acute Ischemic Stroke Patients Taking Dual Antiplatelet Therapy - Guo, Yinping; Zhang, Yi; Zhao, Jing; Wu, Lingshan; Yu, Zhiyuan; He, Dan; Huang, Hao; Luo, Xiang (Frontiers in Neurology, 2021)
Objectives: Diabetes mellitus (DM) is a significant risk factor for ischemic stroke and associated with platelet reactivity. We aim to evaluate the effect of DM on platelet function in acute ischemic stroke patients taking dual antiplatelet therapy (DAPT). Methods: We consecutively included patients with acute ischemic stroke taking DAPT. Platelet function was assessed by thromboelastography and the arachidonic acid (AA) or adenosine diphosphate (ADP) induced platelet inhibition rate were used to confirmed the high-residual on-treatment platelet reactivity (HRPR) to aspirin or clopidogrel. We classified patients into DM and non-DM groups. The association between DM and platelet function was assessed and the confounding factors were adjusted by propensity score matching (PSM) analysis. The independent risk factors of HRPR were determined by multivariate logistic regression analysis. Results: A total of 1,071 acute ischemic stroke patients, 712 in the non-DM group and 359 in the DM group, were included. Patients with DM had a significantly higher maximum amplitude (63.0 vs. 62.0 mm, P < 0.01), ADP-induced clot strength (34.6 vs. 30.3 mm, P < 0.01) and clopidogrel HRPR rate (22.6% vs. 17.3%, P = 0.038) than those without DM. Among 662 patients after PSM, the maximum amplitude (63.1 vs. 62.5 mm, P = 0.032), ADP-induced clot strength (34.6 vs. 29.3 mm, P < 0.01) and clopidogrel HRPR rate (23.0% vs. 15.7%, P = 0.018) is still higher in the DM group. DM was an independent factor of clopidogrel HRPR (OR = 1.48, 95% CI: 1.03–2.07, P < 0.05). Conclusions: In acute ischemic stroke patients taking DAPT, DM is associated with increased platelet reactivity and higher prevalence of clopidogrel HRPR.